Shallow-donor impurity in coupled GaAs/Ga(1-x)Al(x)As quantum well wires: hydrostatic pressure and applied electric field effects (2010)
ABSTRACT: In this work we study the binding energy of the ground state for hydrogenic donor impurity in laterally coupled GaAs/Ga1 xAlxAs double quantum well wires, considering the effects of hydrostatic pressure and under the influence of a growthdirection applied electric field. We have used a variational method and the effective mass and parabolic band approximations. The low dimensional structure consists of two quantum well wires with rectangular transversal section coupled by a central Ga1 xAlxAs barrier. In the study of the effect of hydrostatic pressure, we have considered the G – X crossover in the Ga1 xAlxAs material, which is responsible for the reduction of the height of the confining potential barriers. Our results are reported for several sizes of the structure (transversal sections of the wires and barrier thickness), and we have taken into account variations of the impurity position along the growth-direction of the heterostructure, together with the influence of applied electric fields. The main findings can be summarized as: (i) for symmetric quantum-well wires (QWW) the binding energy is an even function of the growth-direction impurity position and this even symmetry breaks in the case of asymmetric structures; (ii) the coupling between the two parallel wires increases with the hydrostatic pressure due to the negative slope of the confinement potential as a function of pressure; (iii) for impurities in the central barrier the binding energy is an increasing function of the hydrostatic pressure; (iv) depending on the direction of the applied electric field and the fixed impurity position, the binding energy can behave as an increasing or decreasing step function of the applied electric field, and finally (v) for appropriate values of the wires and barrier widths the results reproduce the exact limits of 2D and 3D hydrogenic atom as well as the limits of finite and infinite potential barrier quantum wells.